Empowering Career Choices; Assessing The Impact Of Career Guidance Workshops On Adolescent Careers Self-Efficacy And Goal Setting - Dr. Aqeel Ahmad Khan, Gull Naz Khan, Rabeeya Altaf , Faiza Khalid, Ahmed Ikram, Aamir Iqbal, Bisma Jamil (Migration Letters, 2024)
This study aimed to assess the impact of a career guidance workshop on high school students in Bahawalpur, Punjab, focusing on enhancing career self-efficacy, outcome expectations, career goals, understanding of career pathways, and identifying specific needs and challenges faced by students. Utilizing a mixed-methods approach, quantitative data were collected from 47 students through pre- and post-test measures, including the Career Self-Efficacy Scale, Career Outcome Expectations Scale, and Career Goals Inventory. Additionally, qualitative data were gathered through a Needs Assessment Questionnaire. Results indicated significant improvements in career self-efficacy (p < 0.001), clarity of career goals (p < 0.001), and understanding of career pathways (p < 0.001). However, changes in career outcome expectations were not statistically significant (p = 0.061). Qualitative findings highlighted critical barriers such as limited access to resources, lack of awareness of non-traditional career paths, and socioeconomic challenges. These findings underscore the importance of structured career guidance programs tailored to meet the unique needs of students in Bahawalpur. The study concludes that enhancing access to resources and providing comprehensive career information are essential to support students in their career planning endeavors.